2023
DOI: 10.1021/acs.biomac.3c00162
|View full text |Cite
|
Sign up to set email alerts
|

Role of Membrane Features on the Permeability Behavior of Polymersomes and the Potential Impacts on Drug Encapsulation and Release

Abstract: Self-assembled bilayer structures such as those produced from amphiphilic block copolymers (polymersomes) are potentially useful in a wide array of applications including the production of artificial cells and organelles, nanoreactors, and delivery systems. These constructs are of important fundamental interest, and they are also frequently considered toward advances in bionanotechnology and nanomedicine. In this framework, membrane permeability is perhaps the most important property of such functional materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…A lower permeability would lead to a slower release. 49 As indicated by DLS, the size of both nanoparticles with and without EB decreased with increasing content of SL, which suggested a faster release as the results of a shorter distance that EB molecules had moved from internal region to the surface of the particle. However, the release of EB dropped from the nanoparticle of higher SL content, which indicated that the release was dominated by the absorption capacity of the vehicle.…”
Section: Effect Of Composition Of Nanoparticlementioning
confidence: 82%
“…A lower permeability would lead to a slower release. 49 As indicated by DLS, the size of both nanoparticles with and without EB decreased with increasing content of SL, which suggested a faster release as the results of a shorter distance that EB molecules had moved from internal region to the surface of the particle. However, the release of EB dropped from the nanoparticle of higher SL content, which indicated that the release was dominated by the absorption capacity of the vehicle.…”
Section: Effect Of Composition Of Nanoparticlementioning
confidence: 82%
“…[86] Polymersome membranes usually exhibit low permeability unless they are assembled from selected polymers whose chemical nature results in an inherently porous membrane. [87] For selective permeability, the incorporation of natural channels into the membrane or of chemically/genetically-modified ones to respond to the presence of external stimuli is required to facilitate access of substrates to the encapsulated enzymes. [88,89] Different methods for permeabilizing polymer membranes are discussed below.…”
Section: Polymersomesmentioning
confidence: 99%
“…Hydrophilic polymers such as PEG, , poly­(2-methyl-2-oxazoline) (PMOXA), poly­(acrylic acid) (PAA), and poly­( N -isopropylacrylamide) (PNIPAAm) have been employed as shell-forming blocks in ABCPs (Figure and Table ). The shell-forming block plays a crucial role in providing steric stability to polymersomes during their storage and in vivo circulation.…”
Section: Introduction To Amphiphilic Block Copolymersmentioning
confidence: 99%
“…The separation of the core-forming hydrophobic blocks from the surrounding aqueous media supported by strong cohesive forces is crucial for the formation of stable polymeric systems and incorporation of payloads. In other words, stability is tightly tied to physicochemical properties of the hydrophobic block such as stiffness, crystallinity, cross-linking in the polymer segments, and interactions governing drug incorporation including π–π stacking and electrostatic or hydrogen bonding. Hydrophobic blocks include poly­(butadiene) (PBD), ,, poly­(propylene sulfide) (PPS), poly­(styrene) (PSt), poly­(dimethylsiloxane) (PDMS), and poly­[2-(diisopropylamino)-ethyl methacrylate] (PDPA) (Figure and Table ). Despite their lack of biodegradability, incorporating PEG through conjugation renders the block copolymers biocompatible .…”
Section: Introduction To Amphiphilic Block Copolymersmentioning
confidence: 99%